Effects of family business goals and entrepreneurial behaviour on business performance among Malay small family food processing businesses in Peninsular Malaysia - Jamaluddin, Askiah (2017)
Malay small family businesses (MSFB) in the food processing industry are important for economic and social development. It has been proved that small family businesses are increasing the family income as well as promoting income generation for the community. Even though the business is small in size, the involvement of family members in the food processing industry has improved their families’ quality of life. The food processing industry has encouraged Malays to grasp the opportunity to be self-employed. Therefore, MSFB in the food processing industry is an important topic to study in the field of the family economy and management. There are five specific objectives of this study to explain the effects of family-business goals and entrepreneurial behaviour on business performance among MSFB in Peninsular Malaysia. The first objective is to identify the profile of MSFB in food processing industry. The second objective is to determine the business performance indicators of MSFB in food processing industry. The third objective is to identify the business performance level of MSFB in food processing industry. Fourth objective is to determine the influence of family business goals and entrepreneurial behaviour on business performance. Finally, the study is to determine the role of family-business goals in moderating the influence of entrepreneurial behaviour on business performance. The quantitative approaches using deductive strategy allows the researcher to answer the research objectives. There are 284 respondents from Perak, Selangor, Johor and Terengganu involved in this study. The list of small family business names was collected from the respective Department of Agriculture (DOA) in these states. Then, the researcher developed a sampling frame and used simple random sampling technique to select the sample. The Confirmatory Factor Analysis (CFA) Amos confirmed that sixteen business performance indicators with four domains. The domains are Demand, Agency Support, People and Finance. Then, the descriptive analysis found that business performance level based on respondent’s profile shows that the young business owner has formal education, and no family involvement in family business explains that they have a high level of business performance. In addition, their monthly income is more than RM3000. While, low level of business performance describes that the respondent at the middle age, no formal education and family involvement in the family business. Then, the high level of business performance registration type is a partnership. They use others name as registration for their company name, business age is more than ten years, annual gross income is more than RM300,000 and the number of worker is less than five. Next, multiple regression analysis using the hierarchical method was undertaken. The result shows that family-business goals and entrepreneurial behaviour affected business performance (R² = 0.37). Finally, the result shows that family goals moderate the influence of entrepreneurial behaviour on business performance, while, the business goals do not moderate the influence of entrepreneurial behaviour on business performance. The findings extend the existing knowledge by explaining subjective business performance indicators. In addition, family-business goals are a new element tested in MSFB studies. This has extended the body of knowledge in research related to entrepreneurial behaviour and business performance. This study has provided benefits for small family business researchers, small business advisors, policymakers, small business owners and family members.